(3GdfXGe GdbGfhfi dJQGNjU GdCSdMI h GdPNGFQ h GdQbGHI Qcf GdSHH ajgG (B: s (3OQGSI JWHjbjI ebGQfI (B/ s - (3YeQh jGSQ MSGe GdOjfs; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3jNdU GdHGMK aj gPg GdOQGSI Edi Cf GdJQNjU GdEOGQj eG gh EdG hSjdI Ch CSdhH ef CSGdjH GdEOGQI dJMbjb ZGjGJ GdfXGe GdYGe JeGeB eKd GdbQGQGJ h GdYbhO GdEOGQjI(B: (3EdG Gfg jNJda YfgG aj HYV GdNUGFU h GdSeGJ GdbGfhfjI ceG JNJda GdJQGNjU GdEOGQjI ef MjK GdfhY h ef MjK GdSdWI GdeefhMI ddEOGQI HENJdGa fhY GdfTGW GdPj JQjO JfXjeg(B: (3aJQGNjU GdCSdMI h PNGFQgG gi JQGNjU eJYdbI HJMbjb ZGjGJ GdVHW GdEOGQj dG SjeG ZGjI GdCef GdYGes
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B420-431s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdGSdMI hGdPNGFQs; (3GdMbhb hGdMQjGJ GdYGeIs; (3GdbGfhf Qbe (B394 (3dSfI (B1954s; (3GdJQGNjU GdGOGQjIs; (3GdMjGRI hGdGMQGRs; (3GdMUhd Ydi GdJQNjUs; (3SdWI hRjQ GdOGNdjIs; (3MOhO GdJQNjU HMjGRI GdGSdMIs; (3YhGQV JQGNjU GdGSdMI hPNGFQgGs; (3GQcGf GdbQGQ GdGOGQis; (3GdQbGHI GdbVGFjIs; (3QbGHI GdedGFeI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes